USE OF GOOD TABLE ("WILFLEY TABLE" TECHNIQUE) AS A BENEFFIATION OF GOLD CARRIER MINERALS - Wiwik Dahani; Boanerges Wino Patty; Subandrio Subandrio; Emmy Fatmi Budhya Fatmi Budhya (PETRO:Jurnal Ilmiah Teknik Perminyakan, 2019)
Increasing the level of an extract into a marketable and valuable mineral or beneficiation process can be carried out in various ways, one of which is a table technique ("Wilfley table"). Beneficiation begins with knowing the character of ore through XRD characterization, mineragraphy, SEM-EDS and Fire Assy, Then, the ore is smoothed to a range of ~ 200 mesh and concentrated with rocking table gravity by varying the size of rock fraction, table slope and water discharge. Based on the comparison of XRD characters, mineragraphy, SEM-EDS and fire Assy from the initial seeds and recovery, the results obtained is found to be within the optimum conditions at fraction ~200 mesh size, 3o  elongation table, and water discharge of 14 liters / minute and with gold recovery of 84.48% or increase gold content from 1.32 g / ton to 18.75 g / ton. Based on the optimization, the finer the size of the particles , the higher the level of gold recovery. Nevertheless, the increase in the slope of the table and water discharge can reduce the recovery of gold.